NGHIÊN CỨU CHẾ TẠO VÀ ỨNG DỤNG LaFeO3 KÍCH THƯỚC NANOMET ĐỂ HẤP PHỤ SẮT, MANGAN VÀ ASEN - Đại, Lưu Minh; Nhiệm, Đào Ngọc; Ninh, Vũ Thế; Chức, Phạm Ngọc; Lịm, Dương Thị; Trung, Đỗ Kiên (Vietnam Journal of Chemistry, 2012)
To used nanosized LaFeO3 for adsorbing iron, manganese and arsenic from aqueous solution. The results showed that nanosized of LaFeO3 have absorbing ability for AS (III), AS (V), Fe (III), Mn (II) according to isothermar mode langmuir. The adsorption capacity of LaFeO3 nanosized are 55.09 mg/g for As (III); 60.74 mg/g for As (V); 115.92 mg/g  for  Fe (III); 78.08 mg/g for Mn (II).